Reliability and mechanical performance of timber–concrete composite beams in the non-linear domain - Nabil Daanoune; Nassim Kernou; Mamoun Fellah; Gamal A. El-Hiti (Građevinar)
Different non-linear methods for calculating the reliability and mechanical performance of timber–concrete composite beams connected using threaded steel rods are compared. Two distinct approaches are used and validated using experimental data: a three-dimensional finite-element model developed using ABAQUS and an analytical study using a frozen shear method. The structural reliabilities of the beams were assessed using the MCS, FORM, and SORM methods, in which the geometric and mechanical input characteristics were treated as random variables. Certain parameters significantly affect beam failure, such as the timber’s bending resistance, the concrete’s compressive resistance, and the degree of composite action.